Autogenic Relaxation with Aromaterapy Cendana on The Quality of Sleeping in Patients Diabetes Mellitus Type II - Wijayanti, Lono; Wardani, Erika Martining; Bistara, Difran Nobel (Institut Ilmu Kesehatan STRADA Indonesia, 2019)
Background: Type 2 DM can not be cured, but can be controlled by controlling blood glucose levels and improving sleep quality of sufferers. Decreased sleep quality can cause endocrine and metabolic disorders such as abnormal glucose tolerance, insulin resistance, and reduced response to insulinPurpose: The purpose of this study is to analyze the effect of autogenic relaxation with sandalwood aromatherapy on the quality of sleep in patients with type 2 diabetes mellitusMethod: This research is a Quasy Experiment research pre-post control group design. The population in this study were all type 2 DM DM beneficiaries and the sample used was 60 respondents using simple random sampling. The independent variable is autogenic relaxation with sandalwood aromatherapy while the dependent variable is sleep quality. The data in this study are numerical so that it is analyzed using parametric statistical tests namely paired sample t test and independent sample t test.Results: The results showed that the quality of pre and post sleep based on the Paired t-test obtained p value = 0,000 (p <0.05), and in the intervention group an increase in sleep quality was greater than the control group marked by the t-value of 22 , 40. Based on the independent sample t-test, p = 0,000 was obtained, so it can be concluded that there were significant differences in sleep quality changes between the control and intervention groups.Conclusion: Autogenic relaxation with sandalwood aromatherapy has a positive impact on sleep quality. The use of autogenic relaxation with sandalwood aromatherapy can be considered as one of the interventions in improving sleep quality that can be carried out routinely even on a daily basis especially for people with type 2 diabetes